Contributions to Online Measurement Systems for the investigation of Wastewater Toxicity on Activated Sludge : Luận án TS. Khoa học vật chất: 624401 - Friedrichs, Ferdinand (2019)
The high importance of monitoring the nitrification-respiration in-hibition at wastewater treatment plants (WWTPs) can be justified by the detection of toxic pollution compounds themselves, which are not biologi-cally degradable and are discharged from the WWTP outlet into the envi-ronment. Additionally, according to the standard A QCVN 40/2011/BTNMT the legal limit values for total nitrogen and NH4 are 20 mg L-1 and 5 mg L-1. Due to the discharge of toxic wastewater from the factories to the wastewater treatment plant the nitrification process might be inhibited and hence the legal limit values for total nitrogen and NH4 are exceeded. Furthermore, activated sludge has been used for agricultural purposes over a long time, a contamination of the activated-sludge with toxic compounds makes a further use as e.g. fertilizer not possible. Moni-toring of the nitrification inhibition at WWTP effluent is relevant for WWTP operators because exceeding the legal limits of NH4 or total nitro-gen caused by inhibiting compounds, can lead to penalties or fines being imposed. Nitrifying bacteria are characterized by a high sensitivity to tox-ic compounds and a slow growth rate and hence the protection of these bacteria is of high importance...